(untitled) (PJDOL, 2023)
The current study explored the possible effect of workplace diversity on employees’ performance in Allama Iqbal Open University. The purpose of this study was to assess the effects of workplace diversity on the performance of employees. The sample of study comprised of 105 Head of departments and 545 regular (BPS-2 to15), contractual, daily wagers and laborers employees working in AIOU main campus as well as regional campuses. Stratified random sampling scheme was applied to select the participants. Data was collected through questionnaire. Pearson correlation test and Regression Analysis test was applied to extract the results.